Impaired retinal vessel dilation predicts mortality in end-stage renal disease - Günthner, Roman; Hanssen, Henner; Hauser, Christine; Angermann, Susanne; Lorenz, Georg; Kemmner, Stephan; Matschkal, Julia; Braunisch, Matthias C.; Küchle, Claudius; Renders, Lutz; Moog, Philipp; Wassertheurer, Siegfried; et al. (Circulation research, 2019)
Rationale:Patients with end-stage renal disease are characterized by increased cardiovascular and all-cause mortality because of advanced remodeling of the macrovascular and microvascular beds.Objective:The aim of this study was to determine whether retinal microvascular function can predict all-cause and cardiovascular mortality in patients with end-stage renal disease.Methods and Results:In the multicenter prospective observational ISAR study (Risk Stratification in End-Stage Renal Disease), data on dynamic retinal vessel analysis were available in a subcohort of 214 dialysis patients (mean age, 62.6±15.0; 32% women). Microvascular dysfunction was quantified by measuring maximum arteriolar dilation and maximum venular dilation (vMax) of retinal vessels in response to flicker light stimulation. During a mean follow-up of 44 months, 55 patients died, including 25 cardiovascular and 30 noncardiovascular fatal events. vMax emerged as a strong independent predictor for all-cause mortality. In the Kaplan-Meier analysis, individuals within the lowest tertile of vMax showed significantly shorter 3-year survival rates than those within the highest tertile (66.9±5.8% versus 92.4±3.3%). Univariate and multivariate hazard ratios for all-cause mortality per SD increase of vMax were 0.62 (0.47-0.82) and 0.65 (0.47-0.91), respectively. Maximum arteriolar dilation and vMax were able to significantly predict nonfatal and fatal cardiovascular events (hazard ratio, 0.74 [0.57-0.97] and 0.78 [0.61-0.99], respectively).Conclusions:Our results provide the first evidence that impaired retinal venular dilation is a strong and independent predictor of all-cause mortality in hemodialyzed end-stage renal disease patients. Dynamic retinal vessel analysis provides added value for prediction of all-cause mortality and may be a novel diagnostic tool to optimize cardiovascular risk stratification in end-stage renal disease and other high-risk cardiovascular cohorts.Clinical Trial Registration:URL: http://www.clinicaltrials.gov. Unique identifier: NCT01152892.
Gesehen am 06.04.2020